Exploring alternative surfactants to replace PEG within lipid nanoparticles - Edidovica,Elina (2024)
Over the past decade an increasing amount of studies has demonstrated that PEGylation not only precipitates reductions in drug delivery efficiency but also triggers the immune system to produce antibodies, specifically anti-PEG antibodies. The objective of my thesis is to explore alternative surfactants that could viably replace PEG within lipid nanoparticles. Specifically, Polysorbate 80 (P80), alpha-tomatine, and N-hexadecyl beta-d-maltoside (HDM). The key findings from this research are that smaller particles have formed with combination of phospholipid DOPC and MQ-water. Upon decreasing total lipid concentration a trend could be observed where the size increased with decreased cholesterol concentration. The most stable formulations, from stability study, are the following: 3 and 10% HDM, 2 and 10% tomatine and 3% P80. When analyzing the samples with Cryo-TEM, it was evident that 30 day old samples exhibited less size variation and appeared smaller. Overall, it could also be seen that tomatine formed more simple vesicles than HDM. Some further investigations are needed to explore the impact of different buffers on formulation of LNP. It could be done by varying pH and concentrations of these buffers. Incorporation of cationic lipid into the formulation could be the next step in this research.
Keywords: Lipid nanoparticle; polyethelyne glycol (PEG); alpha-tomatine; N-hexadecyl beta d-maltoside (HDM); DOPC; DPPC; cholesterol; film hydration; stability study; DLS; Cryo-TEM; SAXS; pharmaceutical formulation